Stability of Fixed Point Sets of a Class of Multivalued Nonlinear Contractions - Binayak S. Choudhury; Chaitali Bandyopadhyay (Journal of Mathematics)
We consider a problem of stability of fixed point sets for a sequence of multivalued mappings defined on a metric space converging to a limit function where the convergence is with respect to the Pompeiu-Hausdorff distance. The members of the sequence are assumed to be multivalued almost contractions. We show that the fixed point sets of this sequence of mappings are stable.